2003
DOI: 10.1103/physrevlett.91.167003
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the Peak Effect in a Type-II Superconductor: Multicriticality in the Bragg-Glass Transition

Abstract: We have used small-angle neutron scattering (SANS) and ac magnetic susceptibility to investigate the global magnetic field H vs temperature T phase diagram of a Nb single crystal in which a first-order transition of Bragg-glass melting (disordering), a peak effect, and surface superconductivity are all observable. It was found that the disappearance of the peak effect is directly related to a multicritical behavior in the Bragg-glass transition. Four characteristic phase boundary lines have been identified on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 28 publications
4
12
0
Order By: Relevance
“…At H c2 < H < H c3 superconductivity exists only in surface layers. A similar behavior has been reported in clean Nb, [73][74][75] as well as in MgB 2 . 76 From the inset in Fig.…”
Section: Surface Superconductivity Above H C2 In Nbsupporting
confidence: 79%
See 1 more Smart Citation
“…At H c2 < H < H c3 superconductivity exists only in surface layers. A similar behavior has been reported in clean Nb, [73][74][75] as well as in MgB 2 . 76 From the inset in Fig.…”
Section: Surface Superconductivity Above H C2 In Nbsupporting
confidence: 79%
“…A similar behavior was reported for clean Nb and discussed in terms of a tricritical point. 73 However, it should be noted that our Nb films are in the dirty limit and are affected by the proximity effect with Al. The columnar structure of sputtered Nb films with a large effective surfaceto-volume ratio and columns orientation perpendicular to the film may also enhance the role of surface superconductivity in the out-of-plane magnetic field.…”
Section: Surface Superconductivity Above H C2 In Nbmentioning
confidence: 99%
“…Thus the full width of the transition is dominated by SSC. Although SSC is well known for carefully polished single crystals [7,9], it is usually considered to be insignificant for disordered, rough or inhomogeneous superconducting films because of its assumed fragility and sensitivity to surface conditions [1,6,8,10]. Therefore, observation of a very robust SSC in our strongly disordered polycrystalline films is rather surprising, especially for field perpendicular to the film.…”
Section: Discussionmentioning
confidence: 98%
“…1.69H c2 than bulk superconductivity [1], which can also smear the superconducting transition. Although SSC is quite profound in polished clean superconductors [6][7][8][9], it is usually ignored for disordered, polycrysstaline films because SSC is considered to be very sensitive to the quality of the surface (e.g., surface passivation [8] and order parameter suppression [1]), surface roughness [6,8] and surface scattering [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, recently it has been demonstrated that the SSC is very robust and exists even in polycrystalline films and in perpendicular magnetic fields [21]. Indeed, SSC has been observed in a variety of superconductors, including conventional low-T c [21,[24][25][26], MgB 2 [27,28], and some iron pnictides [29].…”
Section: Introductionmentioning
confidence: 99%